Sound pressure-dependent acoustic absorption by perforated rigid-frame porous materials - Cavalieri Théo; Van Damme Bart (Acta Acustica)
Porous materials are one of the most common classes of sound absorbers for acoustic treatments. However, thin layers of these classical materials are not efficient at absorbing low-frequency sound waves, which is a practical shortcoming. Low-frequency absorption can be improved by perforated screens in combination with an air gap or a classical porous absorber, since they increase the overall tortuosity of the combined system. A less investigated, but in principle similar alternative to achieve high-tortuosity absorbers is perforating initially closed-cell foams. Yet, at high sound pressure levels (SPL), non-linearities of the surface impedance arise due to flow-separation in the vicinity of the perforations. Therefore, it is necessary to adapt existing porous material models for SPL-dependency which is illustrated here for the case of micro-perforated mineral foams. The proposed investigations are carried on experimentally, a foam sample is tested for flow-resistivity as well as for sound absorption at normal-incidence using impedance tube measurements. We furthermore observe and predict the change of effective fluid properties and Johnson-Champoux-Allard (JCA) parameters with respect to SPL. The most significant of them is the increase of static air-flow resistivity, which drastically changes the equivalent density of the porous medium, and has a negative effect on the sound absorption. The proposed model accurately predicts the change in acoustic absorption of rigidly-backed perforated porous treatments.